The Effect of Trust and Perceived Value on Reuse Intention of Linkaja Application Users Mediated by Customer Satisfaction - Al Fatah, Yayan; Rofiq, Ainur; Khusniyah Indrawati, Nur (Journal of World Science, 2023)
This study aims to analyze the role of customer satisfaction in mediating the effect of trust and perceived value on reuse intention. This type of research is explanatory research. The sampling technique used purposive sampling with 120 respondents and was analyzed using Partial Least Square (PLS). Based on the research results, it says that trust affects reuse intention and customer satisfaction, perceived value influences reuse intention and customer satisfaction, customer satisfaction affects reuse intention, and customer satisfaction mediates the effect of trust and perceived value on reuse intention. Customer satisfaction acts as a partial mediating variable. Trust and perceived value influence user intentions to reuse the application. Therefore, LinkAja application management must pay attention to and build trust and perceived value to strengthen user intentions to use the application again. So, it is important to pay attention to customer satisfaction and act as an important mediator in the relationship between trust and perceived value with the intention of reuse.